Effect of heat treatment on the structure and photocatalytic properties of BiYO3 and BiY0.995Ni0.005O3 ceramic powders. Issue 12 (15th August 2020) - Hernández-Arellano, Diana L.; Durán-Álvarez, Juan C.; Zanella, Rodolfo; López-Juárez, Rigoberto
Abstract: BiYO3 powders were synthesized by the Pechini method under low-temperature conditions. When the heat treatment was performed at T < 600 °C, a mixture of tetragonal and cubic phases was obtained, while for T ≥ 600 °C, only the fluorite-like cubic phase was observed. Based on the Rietveld refinement, approximately 2% and 1% of the tetragonal phase remained in samples calcined at 400 °C and 500 °C for 1 h, respectively. The crystal size calculated for these samples was 4.4–48.1 nm, depending on the calcination temperature. The specific surface area of the samples diminished with heat treatment and reached a minimum at 800 °C. The band gap of samples with mixed phases was close to 2.16 eV and was ~2 eV for samples with a cubic phase. Photocatalytic tests demonstrate that BiY0.995 Ni0.005 O3 calcined at 800 °C had the best performance: it degraded more than 80% of the antibiotic oxytetracycline when irradiated with visible light. The Ni-doped BiYO3 material could degrade the antibiotic in tap water at an environmentally relevant concentration (μg L −1 levels) and showed steady activity throughout four reaction cycles.